Specialised (in)security: violence against women, criminal courts, and the gendered presence of the state in Ecuador - Silvana Tapia Tapia; Kate Bedford (Latin American Law Review)
This article asks what the reliance on criminal law and policy to address violence against women (VAW) reveals about the gendered interaction between law, development, and security. Using empirical research on Ecuador’s specialised courts for VAW, we argue that the state’s turn to criminal law—often presented as evidence of taking violence seriously—has in practice resulted in reduced protection for women. The use of penality to address VAW allows courts to prove that women’s safety and security are being taken seriously while concealing–and in some respects fuelling–state abandonment regarding effective protection and services for survivors. We conclude with a call to gender discussions of the turn to criminal law within development and security studies.